Nonverbal Communication Used by Students of Informatics Study Program in Studying English through Lesson Study - Opik Dwi Indah; Juwita Crestiani; Muhammad Affan Ramadhana (Universitas Cokroaminoto Palopo, 2018)
The objective of this research is to know what kinds of nonverbal communication used by the second semester students of Informatics Study Program in studying English at Universitas Cokroaminoto Palopo. This research applied descriptive method. The population of this research is the second semester students of Informatics Study Program class 2P and 2J with the total population is about 70 students. And the participants are 35 students. They were taken by applying purposive sampling technique. In collecting the data, the researcher analyzed the data qualitatively and the instruments used observation checklist and supported by documentation. Based on the observation, the researchers conclude that there are some nonverbal communications that students used in studying English such as: gesture, posture, facial expression and eye contact.